ESTENOSE SUBGLOTICA - Montovani, Jair Cortez [UNESP]; Lopez Ruiz, R. [UNESP]; Castilho, E. C. [UNESP] (My University, 1995)
In the present study we report the experience of the Department of Otolaryngology-Head and Neck Surgery, University Hospital, Botucatu School in 19 cases of laryngotracheal stenosis. Fifteen cases had subglottic stenosis, one had stenosis of inferior tracheal and subglottic, one had stenosis of trachea and two others had extensive involvement of larynx and trachea due to chronic inflammatory disease. In eleven patients a laryngotracheal reconstrutive technique with costal cartilagem graft was performed with good results. The major technical difficulties, occurring mainly in children, were the withdrawal of the cannula of the tracheostomy due to granulation tissue formation and the subglottic partial stenosis after surgical reconstruction.
Subglottic stenosis
Keywords: larynx; stenosis; adult; aged; child; clinical article; female; human; infant; male; subglottic stenosis